2007
DOI: 10.1080/01926230701383194
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanistic Basis for Hepatic Toxicity Induced by an Experimental Chemokine Receptor 5 (CCR5) Antagonist Using a Compendium of Gene Expression Profiles

Abstract: A compendium of hepatic gene expression signatures was used to identify a mechanistic basis for the hepatic toxicity of an experimental CCR5 antagonist (MrkA). Development of MrkA, a potential HIV therapeutic, was discontinued due to hepatotoxicity in preclinical studies. Rats were treated with MrkA at 3 dose levels (50, 250, and 500 mg/kg) for 1, 3, or 7 days. Hepatic toxicity (vacuolation, consistent with steatosis, and elevated serum transaminase levels) was observed at 250 and 500 mg/kg, but not at 50 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
3
0
1
Order By: Relevance
“…Our data (14,15) and those of others (40) demonstrate that RAPA concentrations in the 0.1-1 nM range inhibit HIV and synergize with VCV (this report) in the absence of cell toxicity in vitro, suggesting that RAPA doses lower than the ones used in transplantation will be effective against HIV in patients. Synergistic enhancement of VCV antiviral activity by RAPA may allow the use of a lower VCV effective dose in patients, thus minimizing potential drug toxicities such as hepatotoxicity (34,45,46). VCV dose reductions may prove particularly beneficial in the treatment of HIV patients co-infected with hepatitis C virus or hepatitis B virus (up to 50% of HIV patients in regions where the viruses coexist), because these patients are more likely to experience hepatotoxicity (47).…”
Section: Discussionmentioning
confidence: 99%
“…Our data (14,15) and those of others (40) demonstrate that RAPA concentrations in the 0.1-1 nM range inhibit HIV and synergize with VCV (this report) in the absence of cell toxicity in vitro, suggesting that RAPA doses lower than the ones used in transplantation will be effective against HIV in patients. Synergistic enhancement of VCV antiviral activity by RAPA may allow the use of a lower VCV effective dose in patients, thus minimizing potential drug toxicities such as hepatotoxicity (34,45,46). VCV dose reductions may prove particularly beneficial in the treatment of HIV patients co-infected with hepatitis C virus or hepatitis B virus (up to 50% of HIV patients in regions where the viruses coexist), because these patients are more likely to experience hepatotoxicity (47).…”
Section: Discussionmentioning
confidence: 99%
“…Since that study, Pfizer’s maraviroc 1 was approved for HIV treatment, a backup 2 was identified, and the structures of candidates were disclosed by Merck ( 3 , HIV), , GlaxoSmithKline ( 4 , HIV), and AstraZeneca ( 5) , for rheumatoid arthritis (RA; see Scheme )) . Merck’s 3 was discontinued because of preclinical hepatotoxicity, and clinical development of GlaxoSmithKline’s 4 was stopped. AstraZeneca’s 5 was ineffective clinically in RA, despite providing full blockade of CCR5 function in patients; other CCR5 antagonists including 1 also failed in RA .…”
Section: Examples Of Optimization Trajectory Analysismentioning
confidence: 99%
“…Subsequent publications from the Merck group have indicated the compound to be hepatotoxic in preclinical rat studies at elevated doses, implying a mechanism of mitochondrial inhibition and explaining the discontinuation of Merck A [58]. Subsequent publications from the Merck group have indicated the compound to be hepatotoxic in preclinical rat studies at elevated doses, implying a mechanism of mitochondrial inhibition and explaining the discontinuation of Merck A [58].…”
Section: Merckmentioning
confidence: 99%